Understanding the Public's Viewpoint on Organ Donation Among Adults in Bangladesh: An Exploratory Cross‐Sectional Study - Mst Sabrina Moonajilin; Rajon Banik; Md. Saiful Islam; Kifayat Sadmam Ishadi; Ismail Hosen; Hailay Abrha Gesesew; Paul R. Ward (Health Science Reports)
ABSTRACT Background and Aims Organ donation is the last option for patients with end‐stage organ failure, but the number of people in need of transplantation outweighs the supply of donor organs. A thorough analysis of public understanding is required to design educational programs that increase public commitment to organ donation. Therefore, the present study aimed to explore Bangladeshi adults' understanding, attitudes, and willingness towards organ donation, while also investigating the sources of information, gender‐specific knowledge, intentions, and the factors influencing their decisions. Methods A cross‐sectional survey was conducted between October 15 and November 25, 2021, using a non‐probability convenience sampling technique. Data were analysed using both descriptive and inferential statistics. Results Among 592 participants, only 35.8% were knowledgeable about organ donation. Internet/online sources were the most reported source of knowledge (37.8%), followed by social media (36%). Despite having limited knowledge, 63.7% had a positive attitude, with females demonstrating a more positive attitude than males (β = 0.09, p = 0.024). Males were significantly more likely than females to follow Bangladesh's specific organ donation laws (29.3% vs. 25%, p = 0.004). Besides, 48.6% of females, compared to 40.4% of males, believe that the health service related to organ donation in Bangladesh is ineffective (p = 0.016). More than one‐third (35.1%) of the participants indicated a willingness to donate their organs after death. The participants' significant barriers to organ donation were found to be family objections (40.4%), health complications (34.4%), fear of disfigurement (31.1%), and religious barriers (26.8%). Conclusion Although Bangladeshi adults have a positive attitude regarding organ donation, they lack adequate knowledge, which renders them unlikely to be eager to donate organs. Therefore, it is crucial to update policy within a sociocultural framework to boost organ donation for transplantation. National education campaigns and awareness‐raising events should be held in Bangladesh to increase public knowledge of organ donation and transplants.